Deconstructing product design : exploring the form, function, usability, sustainability, and commercial success of 100 amazing products - Lidwell, William; Manacsa, Gerry (Rockport Publishers, 2009)
"This book deconstructs the design and functional elements and innovations of 100 extremely successful and groundbreaking products. The author profiles them in a succinct bulleted manner, working off the successful format of Universal Principals of Design that it provides consistent types of information in a concise format. Allowing readers to quickly find and understand the workings behind the essential details, some of which made these products stand out and thrive in the crowded marketplace, and some that did not meet their expectations. Every product has a range of elements and even in some successful new designs, there are elements that don't work as well as the designer had hoped. By examining both the good and the bad, readers walk away with an enlightened view of some of today's groundbreaking work" -- Product Description